Socialization of Diaper Waste Composting for the Bojong Indah Parung Community, Bogor District - Refranisa; Estuti Rochimah; Novy Hapsari (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Diaper waste is one of the wastes that is difficult to decompose by soil microbes. The decomposition process takes up to hundreds of years. The large amount of diaper waste that is disposed of carelessly can have a negative impact on the environment. Diaper waste can be used to make useful products. The absorbent gel can be used as plant fertilizer. The gel is very good at absorbing water so that it can retain soil moisture and become a nutrient for plants. However, not many people know the impact of diaper waste and do not know that diaper waste can be made into useful products. There needs to be knowledge about the negative impacts of diaper waste that can pollute the environment. Then continued with the socialization of diaper waste management into plant fertilizer for residents of RT 01/ RW 02 Bojong Indah Village, Parung District, Bogor Regency. The implementation method used is to provide socialization and provide guidance on the stages of processing diaper waste into plant fertilizer.